Divergent Population Trends of Two Sympatric Auk Species in the Rapidly Warming Gulf of Maine - Sarah E. Durham; Sarah P. Saunders; Antony W. Diamond; Thomas V. Riecke; Heather L. Major (Ecology and Evolution)
ABSTRACT Rapidly warming global temperatures are having a widespread influence on wildlife communities across taxa, with southern‐edge populations often experiencing the greatest negative impacts. However, sympatric species may exhibit divergent demographic responses due to differences in life history strategies and niche separation. We used integrated population models to estimate abundance, survival, and productivity for Atlantic Puffins and Razorbills nesting at the southern edge of their breeding range in the rapidly warming Gulf of Maine. We then conducted transient life table response experiments to understand the relative importance of demographic parameters in driving population dynamics. We found that the Atlantic Puffin population remained relatively stable over the 22‐year study period, whereas the Razorbill population increased substantially. Estimates of mean survival and productivity were similar between the study species but were at the lower range of values reported in the literature across their range. Despite similar estimates of mean productivity, interannual variation in this demographic rate was much higher in Puffins than Razorbills. Overall, adult survival was found to be the primary driver of population dynamics for both species yet shows evidence of long‐term decline in Puffins. For Razorbills, we found similar evidence of long‐term decline in first‐year survival. Overall, our findings suggest that these sympatric species may be responding differently to shared environmental conditions. Given the observed long‐term decrease in Puffin adult survival, future monitoring and conservation efforts for this species should be focused outside the breeding season in critical overwintering areas and migratory locations where adult mortality is typically concentrated. Similarly, given the observed long‐term decline in Razorbill first‐year survival, additional monitoring and tracking of chicks is warranted for this species to understand where immature individuals are going after they fledge from the colony.